Projeto preliminar de um separador pneumático de casca/amêndoa da noz pecã - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The south of Brazil has proved to be an important region producing pecans. Due to the increasing demand of the consumer market the region has a high potential for the increase of production. Processing is an important part of the production process, adding value to the product, guaranteeing quality and thus increasing the producer’s income. In this context the work has the objective of realizing the design of a pneumatic peeler of pecan peel for use in a beneficiation line. The equipment must be able to separate the shells and the almond into a continuous operating regime. For this, shell and almond were characterized in order to know parameters such as density, size after breaking, terminal velocity of the particles. An experimental analysis of the terminal velocity of the product was used, from which the design was elaborated. Thus, the separator is designed to operate at an average flow rate of 0:625 m3=s which in the separation column corresponds to a velocity profile with up to 12 m=s. The designed separator features a very compact shape having 2:1 meters high, built in AISI 304 stainless steel and approximate weight of 137 kg, estimated capacity of 300 kg=h of separate product, with centrifugal fan Rear spades driven by electric motor of 0:75 cv.
Keywords: Noz Pecã; Engenharia mecânica; Projeto de máquinas; Separador pneumático; Pecan; Machine Design; Pneumatic separator; Mechanical Engineering; CNPQ::ENGENHARIAS